On the Relation of Shadowing and Expansivity in Nonautonomous Discrete Systems (Analysis in Theory and Applications, 2017)
In this paper we study shadowing property for sequences of mappings on compact metric spaces, i.e., nonautonomous discrete dynamical systems. We investigate the relations of various expansivity properties with shadowing and $h$-shadowing property.